The Influence of Dicipline on The Performance of Employees Work in The Cooperatives and UKM South Sulawesi Province - Friantama Fajar Gunawan; Jamaluddin Jamaluddin; Andi Muhammad Rivai (Public Resource Innovation Management and Excellence, 2025)
This study aims to find out how much Influence Of Discipline On The Performance Of Employees Work In The Cooperatives And UKM South Sulawesi Province. This research uses quantitative research methods. To achieve this goal, researchers use data collection techniques in the form of observations, questionnaires, and documentation. The sample used in this study was 63 employees workers. Data obtained from research results that were processed using data analysis and using the SPSS 25 application consisting of validity and reliability test. Descriptive data analysis techniques. The results of the study show that the indicators used for each of these variables indicate where the discipline is in the very good category. Indicators of performance employees are in the very good category. Based on the test of the determinant coefficient, the influence was strong or high between the two variabels. So it was concluded that the influence of discipline on the performance of employees work in the Cooperatives And UKM South Sulawesi Province is strong or high.